OP0103 Identification of optimal subcutaneous doses of tocilizumab in children with systemic juvenile idiopathic arthritis. (12th June 2018) - Brunner, H.; Ruperto, N.; Lovell, D.; Calvo-Penedes, I.; Horneff, G.; Gamir Gamir, M.L.; Hufnagel, M.; Hsu, J.; Bao, M.; Douglass, W.; Mallalieu, N.L.; Wells, C.; et al.
Abstract : Background: Efficacy and safety of intravenous (IV) tocilizumab (TCZ) were demonstrated in patients (pts) with systemic juvenile idiopathic arthritis (sJIA) in the phase 3 TENDER study 1 (WA18221). Study WA28118 (ClinicalTrials.gov, NCT01904292 ) investigated dosing regimens of subcutaneous (SC) TCZ in pts with sJIA by bridging to IV TCZ data to identify the optimal SC regimen. Objectives: To characterise the pharmacokinetics (PK), pharmacodynamics (PD), and safety of TCZ SC in pts with sJIA; efficacy was an exploratory objective. Methods: This phase 1b multicenter, open-label study evaluated PK, PD, and safety of TCZ SC in pts aged 1–17 years with sJIA and inadequate response to glucocorticoids and nonsteroidal anti-inflammatory drugs. Interim analysis (IA) was conducted after 24 pts had received TCZ SC for 14 weeks. Pts could be either TCZ-naive or switch from TCZ IV to SC at baseline. TCZ SC was administered for 52 weeks according to body weight:<30 kg, either 162 mg every 10 days (before IA) or 162 mg every 2 weeks (Q2W, after IA); ≥30 kg, 162 mg every week (QW). Results: Among enrolled pts (n=51), 25 weighed <30 kg (8 before and 17 after IA) and 26 weighed ≥30 kg. Twenty-six pts (51%) were TCZ naive and 25 (49%) switched from TCZ IV. Median steady state Cmin was similar for pts<30 kg receiving TCZ 162 mg Q2W and those ≥30 kg receiving TCZ 162 mg QW, and the range largely overlapped (table 1). More than 95% (49/51) of pts treated with TCZ SC had model-computed steady state Cmin higher than the 5th percentile achieved with TCZ IV. Median and range of AUC2weeks were similar for both weight groups (table 1). Changes in interleukin-6, C-reactive protein, and erythrocyte sedimentation rate were similar for both weight groups. Most pts had ≥1 adverse event (AE; n=50; 98%). Injection site reactions (ISRs) occurred in 21 pts (41%); most were mild and none led to treatment interruption/withdrawal. AE rate was 1200.3/100 patient-years (PY) (909.3/100 PY excluding ISRs). The most common AEs were viral upper respiratory tract infection (13; 25.5%), neutropenia (13; 25.5%), and cough (12; 23.5%). Nine serious AEs occurred in 7 pts (13.7%; 19.3/100 PY); 5 were infections, all in the <30 kg group. Two deaths occurred, both in the <30 kg group. Median Juvenile Arthritis Disease Activity Score-71 improved (decreased) from baseline to week 52 for TCZ-naive pts (<30 kg, –13.9; ≥30 kg, –12.4) and was maintained or improved further for pts who switched from TCZ IV (<30 kg, –0.7; ≥30 kg –0.2). Conclusions: A PK-based strategy successfully bridged TCZ SC to TCZ IV in pts with sJIA. Dosing regimens of 162 mg Q2W in pts<30 kg and 162 mg QW in pts≥30 kg provided adequate exposure to support efficacy comparable to that of TCZ IV. Except for ISRs, safety was consistent with the known safety profile of TCZ IV in sJIA. Reference: [1] De Benedetti F, et al. N Engl J Med2012;367:2385–2395. Disclosure of Interest: H. Brunner: None declared, N. Ruperto Consultant for: AbbVie, Amgen, Biogenidec, Alter, AstraZeneca, Baxalta Biosimilars, Biogenidec, Boehringer, BMS, Celgene, CrescendoBio, EMD, Speakers bureau: AbbVie, Amgen, Biogenidec, Alter, AstraZeneca, Baxalta Biosimilars, Biogenidec, Boehringer, BMS, Celgene, CrescendoBio, EMD, D. Lovell Grant/research support from: National Institutes of Health, NIAMS, Consultant for: Astra-Zeneca, Bristol Meyers Squibb, AbbVie, Pfizer, Roche, Novartis, UBC, Forest Research Institute, Horizon, Johnson and Johnson, Biogen, Takeda, Genentech, GlaxoSmithKline, Boehringer Ingelheim, Celgene, Janssen, Speakers bureau: Genentech, I. Calvo-Penedes: None declared, G. Horneff: None declared, M. L. Gamir Gamir: None declared, M. Hufnagel: None declared, J. Hsu Employee of: Roche, M. Bao Employee of: Roche, W. Douglass Employee of: Roche, N. L. Mallalieu Employee of: Roche, C. Wells Shareholder of: Roche, Employee of: Roche, C. M. Mela Employee of: Roche, F. De Benedetti Grant/research support from: Novartis, Roche, Pfizer, SOBI, AbbVie, Novimmune, BMS, Sanofi